PERAN AKUN INSTAGRAM USTADZ HANAN ATTAKI DAN EFEKTIVITASNYA SEBAGAI MEDIA DAKWAH DITINJAU DARI TEORI JARUM HIPODERMIK - Khoiru Nisa, Rahmatu Lailia; Fitri, Ahmad Asrof; Abdurrazaq, Muhammad N.; Sulistyani, Anjar (Journal of Islamic Studies, 2023)
This study discusses the role of Ustadz Hanan Attaki's instagram account and its effectiveness as a preaching media in terms of hypodermic needle theory. The problem in this study is how the role of social media account as a media for preaching and its effectiveness according to the hypodermic needle theory in this case is the @hanan_attaki account. This study aims to determine the role of Ustadz Hanan Attaki’s instagram social media account in preaching and see its effectiveness. The method used in this study was a descriptive qualitative approach by taking instagram social media. Data collection techniques were carried out through observation, interviews, and documentation. The sample in this study was taken by means of purposive sampling on followers of @hanan_attaki account. The results of the study showed that the role of Ustadz Hanan Attaki's instagram account as a media for preaching is quite good for followers because it can influence individual behavior in society such as getting information, insight, and entertainment. The effectiveness of the hypodermic needle theory for preaching through the instagram account @hanan_attaki is very effective because it has entered the thoughts and feelings as well as the actions or reactions of followers from @hanan_attaki account which are considered passive and only accept messages conveyed.